Norwegian Shelters for Victims of Domestic Violence in the COVID-19 Pandemic – Navigating the New Normal - Bergman, Solveig (Journal of family violence, 2022)
This study elucidates the responses of shelters and their adaptations to the COVID-19 pandemic, and the effects on their services to victims of violence, as well as how shelter managers assess the situation for victims, including changes in the rates and character of the violence observed by the shelters. A web-based survey was distributed twice to all Norwegian shelters (N = 46): first during the lockdown in spring 2020 and second during the relaxation of infection control measures in summer 2020. The shelters in Norway remained open during the COVID-19 pandemic. The majority saw a reduction in the number of requests during the lockdown, while the rates returned to normal when the strictest infection control measures were lifted. They expressed concern about the decline in requests during the lockdown as well as the well-being of some groups, such as victims from ethnic minority backgrounds, children, and victims with additional challenges. A majority of the shelters did not report changes in the content of the requests. Nevertheless, a third of them had observed instances of the virus and/or infection control measures being used by perpetrators as part of the violence and coercive control strategies. The shelters in Norway, as an integrated part of the welfare state, in general seem to have met the needs of their clients during the pandemic. Yet, the study revealed important inequalities and deficiencies in access to services for some groups, and in the general support and recognition by authorities of the shelters.